Pengaruh Akuntansi Forensik, Audit Investigatif, dan Indepedensi terhadap Pengungkapan Fraud - Avilla Anggun Arisendy; Tri Ratnawati (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to analyze the influence of forensic accounting, audit investigations, independence on fraud disclosure. This research is a literature review, in which we will provide an opinion on the results of previous research. The results of this test are to prove that forensic accounting, investigative auditing and independence will have a significant or insignificant effect on fraud disclosure. It is hoped that the results of this research can enrich the literature for the development of science and also serve as consideration for other researchers.